Analyzing Culture and its Role in Policy Making/Planning for Language Teaching: A Case Study of Teaching Arabic Language in Iran - Mohammad Ali Azarshab; Sadollah Homayuni (̒Ilm-i Zabān, 2016)
Language, as the highest cultural and civilizational phenomenon, is one of the skills acquired through the foreign traditions and community of speakers. Meanwhile, language, as the most important factor in transmitting the past culture and heritage, has a significant role in clarifying and organizing the thoughts and beliefs of society, which is considered as one of the main constituents of identity, personality and culture of societies. Language transaction and cultural and civilizational impacts can be realized throughout history by looking at the intertwined relationships of Arabs and Iranians in different cultural, religious, political, strategic, and other dimensions. These relationships are revealed at two levels of language and culture more than anything else. An important point regarding learning a foreign language is that the cultural approach of communities to foreign languages is influenced by the culture in the broad sense of word. Macro policies of teaching Arabic language in Iran are influenced, intentionally or unintentionally, by this approach and cultural attitudes. In most cases, these attitudes are not consistent with the macro goals and strategies of this field due to cultural, social and political challenges. The present study seeks to analyze the good and friendly linguistic-cultural relations of Arabs and Iranians in the past, and to investigate the causes of the decline of learning Arabic language from two perspectives of culture and language policy making/planning. As such, the present study provides basic approaches and plans to promote teaching Arabic language at both general and specialized levels.